Accommodating receptor flexibility and free energy calculation to reduce false positive binders in the discovery of natural products blockers of SARS-COV-2 spike RBD-ACE2 interface - Marcelina Ogedjo; Isaac Onoka; Mtabazi Sahini; Daniel M. Shadrack (Biochemistry and Biophysics Reports, 2021)
The emergence of severe acute respiratory syndrome coronavirus 2 (SARS-COV-2), which causes coronavirus disease-19 (COVID-19) has caused more than 2 million deaths around the globe. The high transmissibility rate of the disease is related to the strong interaction between the virus spike receptor-binding domain (RBD) and the human angiotensin-converting enzyme 2 (ACE2) as documented in several reports. In this study, using state-of-the-art computational methods, natural products were screened and their molecular mechanism to disrupt spike RBD-ACE2 recognition was evaluated. There is the sensitivity of results to receptor ensemble docking calculations. Binding free energy and MD simulation are important tools to evaluate the thermodynamics of binding stability and the capacity of top hits to disrupt RBD-ACE2 recognition. The free energy profiles provide a slight decrease in binding affinity of the virus-receptor interaction. Three flavonoids parvisoflavone B (3), alpinumisoflavone (5) and norisojamicin (2) were effective in blocking the viral entry by binding strongly at the spike RBD-ACE2 interface with the inhibition constant of 0.56, 0.78 and 0.93 μM, respectively. The same compounds demonstrated similar effect on free ACE2 protein. Compound (2), also demonstrated ability to bind strongly on free spike RBD. Well-tempered metadynamics established that parvisoflavone B (3) works by binding to three sites namely interface α, β and loop thereby inhibiting viral cell entry. Owing to their desirable pharmacokinetic properties, the presented top hit natural products are suggested for further SARS-COV-2 molecular targets and subsequent in vitro and in vivo evaluations.